Innovative component of economic security of enterprises: a case of the Republic of Moldova - Ianioglo, Alina; Polajeva, Tatjana (Journal of Business Economics and Management, 2017)
In modern conditions of unpredictability, issues of ensuring the economic security of enterprise become particularly important and innovations are a significant component. The article aims to advance the knowledge of economic security and to develop the methodology of ensuring the economic security of enterprise and its innovative component. To achieve this goal, the following methods were used: systematization, data collection, analysis, comparison and the inductive method. The system of ensuring economic security was developed and the mechanism of increasing the innovative activity of enterprises in developing countries was determined, on example of the Republic of Moldova. The presented research results are important for the development of economic science as they represent a systematization of different approaches to economic security with the focus on its innovative component. The developed system, with its main phases and proposed measures, may be implemented by the management in order to strengthen the innovative activity and the economic security of enterprises, taking into account the features of a specific industry and the environment of a specific country.